Effects of land clearing for agriculture on soil organic carbon stocks in drylands: A meta‐analysis. Issue 2 (28th October 2022) - Wang, Yuangang; Luo, Geping; Li, Chaofan; Ye, Hui; Shi, Haiyang; Fan, Binbin; Zhang, Wenqiang; Zhang, Chen; Xie, Mingjuan; Zhang, Yu
Abstract: Agricultural activities have been expanding globally with the pressure to provide food security to the earth's growing population. These agricultural activities have profoundly impacted soil organic carbon (SOC) stocks in global drylands. However, the effects of clearing natural ecosystems for cropland (CNEC) on SOC are uncertain. To improve our understanding of carbon emissions and sequestration under different land uses, it is necessary to characterize the response patterns of SOC stocks to different types of CNEC. We conducted a meta‐analysis with mixed‐effect model based on 873 paired observations of SOC in croplands and adjacent natural ecosystems from 159 individual studies in global drylands. Our results indicate that CNEC significantly ( p < .05) affects SOC stocks, resulting from a combination of natural land clearing, cropland management practices (fertilizer application, crop species, cultivation duration) and the significant negative effects of initial SOC stocks. Increases in SOC stocks (in 1 m depth) were found in croplands which previously natural land (deserts and shrublands) had low SOC stocks, and the increases were 278.86% (95% confidence interval, 196.43%–361.29%) and 45.38% (26.53%–62.23%), respectively. In contrast, SOC stocks (in 1 m depth) decreased by 24.11% (18.38%–29.85%) and 10.70% (1.80%–19.59%) in clearing forests and grasslands for cropland, respectively. We also established the general response curves of SOC stocks change to increasing cultivation duration, which is crucial for accurately estimating regional carbon dynamics following CNEC. SOC stocks increased significantly ( p < .05) with high long‐term fertilizer consumption in cleared grasslands with low initial SOC stocks (about 27.2 Mg ha −1 ). The results derived from our meta‐analysis could be used for refining the estimation of dryland carbon dynamics and developing SOC sequestration strategies to achieve the removal of CO2 from the atmosphere. Abstract : To characterize the effects of clearing natural ecosystems for cropland (CNEC) on soil organic carbon (SOC) stocks, we conducted a meta‐analysis with mixed‐effect model. Result indicates that CNEC significantly affects SOC stocks, resulting from a combination of natural land clearing, cropland management practices and the significant negative effects of initial SOC stocks. The increases in SOC stocks were 278.86%, 45.38%, ‐24.11%, ‐10.70% in clearing deserts, shrublands, forests and grasslands for cropland, respectively. We also established the general response curves of SOC stocks change to increasing cultivation duration, which is crucial for accurately estimating regional carbon dynamics following CNEC.